Psychological pitfalls and the next financial crisis - Henning Klodt (The crisis and beyond, 2009)
Since the economic downturn started, exports have fallen dramatically and rapidly. One reason for this is the importance of vertical specialization, where the drop in demand for the final good induces a domino effect on to demand for intermediate inputs. Hence, the strong collapse in exports in the recent month is at least partly driven by the same forces that allowed global trade to expand much faster than global GDP in the last two decades, i.e. global production networks. One view is that after the crisis, these networks will bounce back and trade will be back to normal quite rapidly. We point out, however, that this may be an overly optimistic view. Building global production networks involves substantial set up costs that are often nonrecoverable. These might be sunk costs of exporting or sunk costs of foreign sourcing of inputs. The existence of such costs may make is unlikely that international trade relationships will restart as quickly once the economic situation improves again. Hence, the international crisis may have consequences that go well beyond the prediction of a standard economic model, when the presence of global production networks and sunk costs of building foreign trade nodes are taken into account.
Keywords: 330; Bubbles; Finanzmarktkrise; Sozialpsychologie; Verhaltensökonomik; Kognition